ANALISIS PELAKSANAAN PEMBELAJARAN TATAP MUKA PASCA PANDEMI COVID-19 DALAM MENINGKATKAN PRESTASI SISWA - Jefryadi, Jefryadi; Sari, Meilida Eka; Komsi, Dwi Noviana; Adiya N, Riska Utami (Program Studi Pendidikan Guru Madrasah Ibtidaiyah STAINU Purworejo, 2023)
An educator in carrying out learning activities must make careful preparations. By making careful preparations, educators can carry out learning in the right steps. Based on the results of observations with teachers, students and guardians of grade V students that student achievement in implementing face-to-face learning after the Covid-19 pandemic is still not in line with expectations, there are still some students whose interest in learning is reduced and some guardians play a reduced role in encouraging student achievement in learning. The formulation of the problem in this study is: (1) How is the implementation of face-to-face learning after the Covid-19 pandemic in improving the achievement of fifth grade students at MIT UMMI Lubuklinggau, (2) What are the advantages and disadvantages of implementing face-to-face learning after the Covid-19 pandemic at MIT UMMI Lubuklinggau. In this study using face-to-face learning after the Covid-19 pandemic. This is face-to-face learning after the covid-19 pandemic qualitative method. This qualitative research is research on descriptive research in the form of written or spoken words from people and the observed behavior according to the facts in the field. This research was conducted at MIT UMMI Lubuklinggau. Collecting data with the method of observation, interviews, and documentation. The subjects of this study were 6 main informants, 3 key informant educators for grade V, 1 school principal and 6 guardians of supporting informants. The results of the study show that through face-to-face learning after the Covid-19 pandemic students feel happy, excited, active and easier to understand in improving student achievement and realizing it in life when learning has increased where students can follow and apply it well in everyday life.